2016
DOI: 10.1017/s0376892916000151
|View full text |Cite
|
Sign up to set email alerts
|

Forest foods and healthy diets: quantifying the contributions

Abstract: SUMMARYForested landscapes provide a source of micronutrient rich food for millions of people around the world. A growing evidence base suggests these foods may be of great importance to the dietary quality of people living in close proximity to forests -especially in communities with poor access to markets. Despite widespread evidence of the consumption of forest foods around the world, to date, few studies have attempted to quantify the nutritional contributions these foods make. In this study we tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 45 publications
2
80
0
1
Order By: Relevance
“…The relationship which emerges from the analysis of other cases is that households closer to this type of asset are worse off than others because they may have lower access to social services and infrastructure in general (Wunder et al 2014a). Another dimension is that the types of food resource extracted from forest tend not to be associated with staple foods, with the exception of some roots, limiting their impact from a caloric intake point of view (Rowland et al 2016). However, other studies have shown that households with access to forest as a CR may be better off than other households sharing similar characteristics of isolation, but without access to forest as a CR (Clements et al 2014), highlighting the need for further investigation of this dimension.…”
Section: Model Results: Common Resourcesmentioning
confidence: 99%
See 4 more Smart Citations
“…The relationship which emerges from the analysis of other cases is that households closer to this type of asset are worse off than others because they may have lower access to social services and infrastructure in general (Wunder et al 2014a). Another dimension is that the types of food resource extracted from forest tend not to be associated with staple foods, with the exception of some roots, limiting their impact from a caloric intake point of view (Rowland et al 2016). However, other studies have shown that households with access to forest as a CR may be better off than other households sharing similar characteristics of isolation, but without access to forest as a CR (Clements et al 2014), highlighting the need for further investigation of this dimension.…”
Section: Model Results: Common Resourcesmentioning
confidence: 99%
“…As the survey is representatively based on a national census, its sampling procedure avoids the general bias associated with more specific case studies on wild resources (i.e. PENbased analyses which focus on communities related to forests, such as those of Wunder et al (2014b) and Rowland et al (2016). The sample of households was surveyed in 2012 and 2013.…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations